Footstep power generation using piezoelectric transducers - Lim, Chee Hong; NajibAl-Fadhali; Majid, Huda; Gismalla, MSM; Mukred, Jameel A. A.; Najmaddin Abo Mosali (Progress in Engineering Application and Technology, 2022)
The demand for using electricity is increasing day by day, and generating electricity from green resources is becoming heavy. Therefore, harvesting wasted energy is one of the methods to solve the power generation issue. The wasted energy produced in surrounding such as vibration especially in the popular area. The piezoelectric effect is about, when a certain material applied force on it, it will generate a voltage on the surface. This effect achieved free energy, no pollution issue and simple. Therefore, the purpose of this project “footstep power generation by using piezoelectric transducers” is to produce a voltage by using piezoelectric effect to power low voltage electric application or charge battery. The Material for piezoelectric is ceramic, ceramic has a strong structure and produces more voltage compared with polymer. The piezoelectric effect happens when people walk or step on the tiles that installed the piezoelectric disc. Piezoelectric disc deform and generate electric, for stable the electric generated, AC-to-DC is required. Full-wave bridge rectifier converts voltage from positive and negative cycle to DC, since the output is DC voltage, it able to supply low DC electric application or charge battery. The number and connection of piezoelectric transducers respond to output voltage, the greater number of piezoelectric transducers the greater the output voltage produced. And proven 150 steps on the piezoelectric tiles charged 0.30v to 12V 7.2Ah battery by using this technique, to charge fully battery 6000 steps (approximately). The voltage stored in the battery is DC voltage. An inverter is used to invert DC voltage from battery to AC voltage. The DC-to-AC inverter of this project uses IC SG3526A, SG3526A produce 50hz signal to feed MOSFET and amplify voltage from 12V to 240V by using center tapped transformer. the performance of inverter is successfully applied to below 60W electric application, with adding MOSFET and replace the transformer with 12V 10A is possible to supply to 120W maximum